Avaliação quantitativa da recarga das águas subterrâneas na bacia escola do campus da UFSM - Löbler, Carlos Alberto (2015)
The Campus of UFSM (Universidade Federal de Santa Maria) is supplied mainly by groundwater, captured at outcrop zones (ZA) of the Guarani Aquifer System (GAS). In this sense, the present study aimed to fill the lack of quantitative information of groundwater in the UFSM Basin Campus School. The aims of this study were: 1) Perform recharge estimation of water table in single-well, using the Water Table Fluctuation method. 2) Execute statistical analysis on weekly data levels, monitored since May 2010, identifying possible correlations with rainfall data s and analysis on weekly data levels, and 3) Quantify the areas sealed in bowl using ArcGIS software and Google Earth images of 2007 to 2010. The results of the study indicated a 17.0% to 48.0% infiltration rate of the total precipitation in FATEC old well, whereas an average of 36.0% of rainfall contributes to aquifer recharge. The investigation of soil sealing, performed with data from 2007 to 2014 showed an increase of 24.32 ha in the sealed area during the study period. In the static analysis of correlation of weekly levels with volumes of rain, it was observed that the rains recorded in the measurement date were those of major influences on monitored levels, indicating the replacement level. Regarding the fluctuating levels trends from a total of eight wells monitored, two had drawdown trend. The seasonal analysis showed that levels of the seasons of winter and autumn were those with more water stored in the aquifer, while in summer and spring the opposite happened. As a conclusion, despite the sealed areas had a significant and rapid growth for the Basin, wherein this growth has not specified losses in volumes of recharges groundwater. Once the correlation data between rain and water levels were positive, the level variation trends indicated two of the eight wells with loss of water volume during the monitoring.